It's not always depression : a new theory of listening to your body, discovering core emotions and reconnecting with your authentic self - Hendel, Hilary Jacobs (Penguin Books, 2018)
How can it be that a seemingly depressed person, one who shows clinical symptoms, doesn't respond to antidepressants or traditional psychoanalytical methods of therapy? Hilary Jacobs Hendel shows how we should focus not on CBT or medication but on our emotions as a direct pathway to healing psychological suffering. We were all taught our thoughts affect our emotions but in truth it is largely the other way around: we have to experience our emotions to truly understand our thoughts and our full selves. In It's Not Always Depression, she reveals her most effective techniques for putting us back in touch with the emotions we too often deny, thwart or exclude for fearing we won't be accepted or loved -- methods which can be used by anyone, anytime, anywhere. Drawing on stories of her own practice, Jacobs Hendel sheds light on the core emotions (anger, fear, sadness, joy) and inhibitory emotions (anxiety, shame), how they manifest in the body, and how by employing "accelerated experiential dynamic psychotherapy" (AEDP) we can return to mental wellbeing. Our feelings are a compass for living; reacquaint yourself with them, and recover a vital, more engaged, more authentic self.